Дослідження якості захисту конфіденційності інтернету речей із підтримкою 5G - Пугач, К. О. (ХНУРЕ, 2023)
The Internet of Things (IoT) is becoming increasingly common in our society as the basis of smart homes and other smart environments. IoT refers to a global network that connects real physical objects with the virtual world. In such an environment, 5G cellular networks play a key role. Distinctive features such as high bandwidth, simple and cost-effective connectivity, etc. make the 5G cellular network an ideal candidate to be used as a backbone network in the future smart environment.
Keywords: інтернет речей; захист конфіденційності